Adolescents under Pressure: A New Durkheimian Framework for Understanding Adolescent Suicide in a Cohesive Community. (October 2016) - Mueller, Anna S.; Abrutyn, Seth
Despite the profound impact Durkheim's Suicide has had on the social sciences, several enduring issues limit the utility of his insights. With this study, we offer a new Durkheimian framework for understanding suicide that addresses these problems. We seek to understand how high levels of integration and regulation may shape suicide in modern societies. We draw on an in-depth, qualitative case study ( N = 110) of a cohesive community with a serious adolescent suicide problem to demonstrate the utility of our approach. Our case study illustrates how the lives of adolescents in this highly integrated community are intensely regulated by the local culture, which emphasizes academic achievement. Additionally, the town's cohesive social networks facilitate the spread of information, amplify the visibility of actions and attitudes, and increase the potential for swift sanctions. This combination of cultural and structural factors generates intense emotional reactions to the prospect of failure among adolescents and an unwillingness to seek psychological help for adolescents' mental health problems among both parents and youth. Ultimately, this case illustrates (1) how high levels of integration and regulation within a social group can render individuals vulnerable to suicide and (2) how sociological research can provide meaningful and unique insights into suicide prevention.